Characterizing the Outburst of the Supermassive Black Hole in M87. Issue Volume 14:Issue S342(2018) (May 2018) - Forman, William; Churazov, Eugene; Heinz, Sebastian; Jones, Christine; Nulsen, Paul; Kraft, Ralph; Randall, Scott; Vikhlinin, Alexey
Abstract: M87, in the Virgo cluster, allows us to study the interaction of a supermassive black hole (SMBH) with its hot gaseous atmosphere. Deep Chandra observations reveal a nearly circular shock front with a Mach number of 1.2 and a radius of 13 kpc which is driven by a central cavity inflated by an SMBH outburst began 12 million years ago. An outburst with an energy of a 5×57 ergs and a duration of 2 Myrs provides a good match to all the constraints. For an outburst repetition rate of about 12 Myrs (the outburst age), the outburst energy is sufficient to balance the radiative cooling of the gas. The outburst duration in M87 argues for a "gentle" (long duration) outburst that does not generate strong shocks and where much of the outburst energy is deposited in the cavities that then transfer energy to the surrounding gas as they buoyantly rise.